2001
DOI: 10.1103/physreva.64.032701
|View full text |Cite
|
Sign up to set email alerts
|

Collisional destruction of anionic carbon and silicon clusters by helium, neon, and argon atoms at intermediate velocities

Abstract: We measured the total destruction cross sections of small X n Ϫ clusters (XϭSi and C; nϭ2, 3, and 4͒ in noble gas targets ͑Y ϭ He, Ne, and Ar͒, with relative velocities v in the 0.10-0.95 a.u interval for silicon, and in the 0.20-1.20 a.u. interval for carbon. The measured values increase monotonically with target and projectile sizes, as expected on a geometrical basis. In particular the dependence of the cross sections on n is linear for carbon clusters, agreeing with a quantitative model based on the linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Hence, the improved ratios increase with decreased velocity. It was reported that destruction cross-section ratios of two different gases were smooth functions of the velocity and were essentially projectile independent ͑e.g., independent of cluster sizes͒, 8 and the ratios slightly increased or are almost constant with increased velocity in the range covered with our experiment. In our case, the improved ratios should be related to both the destruction and the production cross-sections.…”
Section: Transmission Measurement and Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Hence, the improved ratios increase with decreased velocity. It was reported that destruction cross-section ratios of two different gases were smooth functions of the velocity and were essentially projectile independent ͑e.g., independent of cluster sizes͒, 8 and the ratios slightly increased or are almost constant with increased velocity in the range covered with our experiment. In our case, the improved ratios should be related to both the destruction and the production cross-sections.…”
Section: Transmission Measurement and Resultssupporting
confidence: 59%
“…3 The stripper gas species should also play an important role because a destruction cross-section of a cluster ion on colliding with the target gas could depend on the state of the outermost electrons. 8 Although there have been some transmission experiments made on several gaseous species for monoatomic ion incidence, 9,10 those on cluster ion incidence are yet to have provided sufficient information. The transmissions were measured using the carbon cluster ions ͑C 4 , C 8 , and C 10 ͒ frequently used in irradiation experiments at our facility on several stripper gases ͑He, N 2 , CO 2 , and SF 6 ͒ of differing molecular size and condition of the valence band electrons in investigating a suitable gas for use in accelerating cluster ions with a tandem accelerator.…”
Section: Transmission Of Cluster Ions Through a Tandem Accelerator Ofmentioning
confidence: 99%
“…Similar measurements have been performed in our laboratory over the last few years (Luna et al 2001a, 2001b, Zappa et al 2001, 2003a, 2003b, Barros et al 2005, Sant'Anna et al 2004, 2006a, 2006b, with a variety of anionic projectiles and gas targets, showing an amazing regularity and clear correlation with the dynamics of the total scattering of free electrons. This similarity pointed to the presence of an underlying dominant physical process in the intermediate-to-high velocity region.…”
Section: Introductionsupporting
confidence: 64%
“…The experiments were performed in a 1.7 MV 5SDH NEC Pelletron tandem accelerator, as described in detail elsewhere (Zappa et al 2001), and only a brief description of the experimental method is given here. A cesium sputtering ion source produces anions which are pre-accelerated to a kinetic energy E 0 in the source (in the 10-20 keV energy range) and undergo velocity selection by a Wien filter.…”
Section: Experimental Methods and Experimental Resultsmentioning
confidence: 99%
“…Details about the method and our experimental setup were given in previous publications [31][32][33][34][35][36][37], and only the main features are described here. The method is based on the use of the high-voltage terminal as the collision chamber, with the collision target being what is traditionally used only as a gas stripper to produce positive ions and neutral species at the second stage of the accelerator.…”
Section: B Measurement Of Total Detachment Cross Sectionmentioning
confidence: 99%